2021
DOI: 10.1111/jace.18004
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of coatings on SiC fibers and their effects on microstructure and mechanical properties of SiCf/SiBCN composites

Abstract: In this study, the amorphous C, ZrB 2 , and BN single-layer coatings as well as C/ BN, C/ZrB 2 , ZrB 2 /BN, and C/ZrB 2 /BN composite coatings were prepared on SiC fibers (SiC f ) by an in situ synthesis and solution impregnation-pyrolysis method.Subsequently, SiC f /SiBCN composites were fabricated by hot-pressing sintering at 1900℃/60 MPa/30 min to explore the influence of different coatings on the microstructure and mechanical performance of resulting composites. After the preparation of single-layer-coated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Compared with continuous carbon fiber reinforced polymer-derived SiBCN (PDCs-SiBCN) ceramic matrix composites (CMCs), [18][19][20][21] short carbon fibers are more suitable for the reinforcement of SiBCN ceramics prepared by mechanical alloying of mixed powders followed by sintering, 4,22,23 because short carbon fibers can be dispersed into mechanically alloyed SiBCN powders by a special sintering technique to obtain short carbon fiber reinforced mechanically alloyed SiBCN (MA-SiBCN) CMCs, denoted as C sf /SiBCN. [24][25][26][27] Zhu et al 26 fabricated C sf /SiBCN containing Zr by sintering under hot-pressing (HP) conditions at 1900 • C. The fracture surface (FS) showed limited fiber pull-out length due to severe interface reaction at high sintering temperatures, and the flexural strength decreased compared with the pure ceramics because of agglomeration and degradation of the carbon fibers. Niu et al 25 also adopted a similar method to obtain C sf /SiBCN and the results showed that many defects, such as pores and cracks, were formed due to uneven dispersion of the short fibers in the matrix as well as due to severe degradation of the fibers caused by interface reaction at high sintering temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with continuous carbon fiber reinforced polymer-derived SiBCN (PDCs-SiBCN) ceramic matrix composites (CMCs), [18][19][20][21] short carbon fibers are more suitable for the reinforcement of SiBCN ceramics prepared by mechanical alloying of mixed powders followed by sintering, 4,22,23 because short carbon fibers can be dispersed into mechanically alloyed SiBCN powders by a special sintering technique to obtain short carbon fiber reinforced mechanically alloyed SiBCN (MA-SiBCN) CMCs, denoted as C sf /SiBCN. [24][25][26][27] Zhu et al 26 fabricated C sf /SiBCN containing Zr by sintering under hot-pressing (HP) conditions at 1900 • C. The fracture surface (FS) showed limited fiber pull-out length due to severe interface reaction at high sintering temperatures, and the flexural strength decreased compared with the pure ceramics because of agglomeration and degradation of the carbon fibers. Niu et al 25 also adopted a similar method to obtain C sf /SiBCN and the results showed that many defects, such as pores and cracks, were formed due to uneven dispersion of the short fibers in the matrix as well as due to severe degradation of the fibers caused by interface reaction at high sintering temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the brittleness issue, reinforcement with fibers is one of the most effective methods to improve the toughness of SiBCN matrices. Compared with continuous carbon fiber reinforced polymer‐derived SiBCN (PDCs‐SiBCN) ceramic matrix composites (CMCs), 18–21 short carbon fibers are more suitable for the reinforcement of SiBCN ceramics prepared by mechanical alloying of mixed powders followed by sintering, 4,22,23 because short carbon fibers can be dispersed into mechanically alloyed SiBCN powders by a special sintering technique to obtain short carbon fiber reinforced mechanically alloyed SiBCN (MA‐SiBCN) CMCs, denoted as C sf /SiBCN 24–27 …”
Section: Introductionmentioning
confidence: 99%
“…Li has studied the effects of on fibers coatings on microstructure and mechanical properties of SiC f /SiBCN composites, and the result shows that the SiC f with coating can improve the mechanical properties, but the effect is limited because SiC fiber with or without protective coatings both crystallized seriously leading to the great strength loss of fibers. 20 Compared with SiC fiber, carbon fiber can maintain strength at higher temperatures, so the interface layer in C f /SiBCN composite has an important rule on mechanical properties. However, the microstructure control of carbon fiber/matrix interface, sintering densification, and their effects on mechanical/thermal shock properties and failure mechanisms of C f /SiBCN are less studied.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, compared with organic method, due to high temperature and high pressure, the interface layer will protect carbon fiber from more serious mechanical damage and corrosion in the hot‐pressing process. Li has studied the effects of on fibers coatings on microstructure and mechanical properties of SiC f /SiBCN composites, and the result shows that the SiC f with coating can improve the mechanical properties, but the effect is limited because SiC fiber with or without protective coatings both crystallized seriously leading to the great strength loss of fibers 20 . Compared with SiC fiber, carbon fiber can maintain strength at higher temperatures, so the interface layer in C f /SiBCN composite has an important rule on mechanical properties.…”
Section: Introductionmentioning
confidence: 99%